Identification of iron-chelating phenolics contributing to seed coat coloration in soybeans (Glycine max (L.) Merr.) expressing aryloxyalkanoate dioxygenase-12. (April 2020) - Cicchillo, Robert M.; Beeson, William T.; McCaskill, David G.; Shan, Guomin; Herman, Rod A.; Walsh, Terence A.
Abstract: Soybeans ( Glycine max (L.) Merr.) genetically modified to express aryloxyalkanoate dioxygenase-12 (AAD-12), an enzyme that confers resistance to the herbicide 2, 4-D, can sometimes exhibit a darker seed coat coloration than equivalent unmodified soybeans. The biochemical basis for this coloration was investigated in a non-commercial transgenic event, DAS-411Ø4-7 that exhibited more pronounced AAD-12-associated seed coat coloration than the commercial event, DAS-444Ø6-6. Analysis of color-enriched seed coat fractions from DAS-411Ø4-7 showed that the color was due to localized accumulation of iron-chelating phenolics, particularly the isoflavone genistin, that are associated with seed coat pectic polysaccharide and produce a brown chromophore. The association between genistin, iron, and pectic polysaccharide was characterized using a variety of analytical methods. Darker seeds from commercial soybean event DAS-444Ø6-6 also show higher genistin content localized to the darker colored portions of the seed coat (with no increase in whole seed genistin levels). Graphical abstract: Image 1 Highlights: Expression of the herbicide resistance gene aad-12 in soybeans can result in subtle seed coat coloration. The chromophore responsible for this coloration was enriched and characterized by multiple analytical methods. The coloration was due to localized accumulation of iron-chelating phenolics, particularly the isoflavone genistin. No overall increase in isoflavones in AAD-12-containing whole soybean seeds were observed. This is, to our knowledge, a previously undescribed molecular basis for seed coat coloration in soybean and other legumes.